Smart materials for drug delivery and cancer therapy. Issue 2 (4th December 2020) - Yang, Yao; Zeng, Weiwei; Huang, Ping; Zeng, Xiaowei; Mei, Lin
Abstract: Until now, enormous smart materials have been engineered with endogenous stimulators such as pH, reactive oxygen species, glutathione, hypoxia and enzyme, or exogenous stimulators such as temperature, light, ultrasound, radiation, and magnetic field in drug delivery. As footstone of stimuli‐responsive nanocarriers, endogenous/exogenous responsive smart materials possess many properties, such as responding ability to specific triggers, controlled drug release, long blood circulation, increased tumor accumulation, "ON‐OFF" switch activities, enhanced diagnostic accuracy, and therapeutic efficacy. Smart materials have attracted considerable attention because they provide likelihood strategy for individualized and comprehensive therapy. In this review, significant research achievements of smart materials responsive to different triggers including their synthesis and formulation mechanism, responsive mechanism, applications, multiple functions are summarized and discussed separately. We primarily focus on the studies in the past few years (2017‐2020). The current situation and remaining challenges of stimuli‐sensitive materials‐based nanocarriers for clinical translation are discussed rationally at the end. It is hope that this timely and overall review would provide some helpful information for researchers in this field. Abstract : Smart Materials in Drug Delivery have attracted considerable attention for precision cancer chemotherapy as the footstone of stimuli‐responsive nanocarriers. Numerous smart materials are delicately designed with time‐/space‐controlled drug release while responsive to either endogenous or exogenous signals. Their advanced achievements range from preclinical studies to commercialized products. All the latest information has been comprehensively summarized herein.